Spatial Inequality and Economic Development : Theories, Facts, and Policies - Kim, Sukkoo (World Bank, Washington, DC, 2017)
Spatial inequality is an important feature of many developing countries that seems to increase with economic growth and development. At the same time, there seems to be little consensus on the causes of spatial inequality and on a list of effective policy instruments that may foster or reduce spatial inequality. This paper examines the theoretical and empirical literature on spatial inequality to learn what we know and do not know about the causes of spatial inequality, to investigate what policies may or may not ameliorate spatial inequality, and to determine whether policy makers can identify and implement policies that promote or reduce spatial inequality.